Profil Kemampuan Literasi Sains Berdasarkan Kecenderungan Gaya Belajar Siswa SMP - Iin Pratiwi; Andika Kusuma Wijaya; Haris Rosdianto (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
This study aims to: (1) analyze the profile of science literacy ability of junior high school students in general; (2) analyzing the learning style of junior high school students; and (3) analyze the science literacy abilities of junior high school students based on their learning style tendencies. This type of research is survey research with a descriptive approach. The data analysis technique used is quantitative descriptive analysis, where the data results will be presented in the form of pie charts and tables to facilitate the interpretation of the information obtained. Respondents in this study were selected through cluster sampling techniques, with a population consisting of all students of SMP Negeri 1 Singkawang. The data collection technique uses two main instruments, namely the science literacy ability test and a questionnaire to measure the tendency of students' learning styles in physics learning. The learning styles identified refer to the VARK (Visual, Auditory, Reading/Writing, and Kinesthetic) model, as well as the grouping between unimodal and multimodal learning styles. The results showed that the multimodal learning style was more dominant (61%) compared to the unimodal learning style (39%). Among the multimodal categories, the quadmodal learning style (using all four aspects of VARK) occupies the largest portion. In addition, it was found that 1 in 3 students had a complete VARK learning style tendency, making it the most common type. Based on further analysis, students with multimodal learning styles—especially quadmodal—have higher average science literacy skills compared to students who have only one type of learning style modality. These findings show that the diversity of learning approaches can have a positive impact on the mastery of science literacy.